New insights into microbial bile salt hydrolases: from physiological roles to potential applications - Dong, Zixing; Yang, Shuangshuang; Tang, Cunduo; Li, Dandan; Kan, Yunchao; Yao, Lunguang (Frontiers in Microbiology, 2025)
Gut microbiota has been increasingly linked to metabolic health and diseases over the past few decades. Bile acids (BAs), the major components of bile, are bidirectionally linked to intestinal microbiota, also known as the gut microbiome-BA metabolic axis. Gut microbiota-derived bile salt hydrolase (BSH, EC 3.5.1.24), which catalyzes the “gateway” reaction in a wider pathway of bile acid modification, not only shapes the bile acid landscape, but also modulates the crosstalk between gut microbiota and host health. Therefore, microbial BSHs exhibit the potential to directly or indirectly influence microbial and host physiologies, and have been increasingly considered as promising targets for the modulation of gut microbiota to benefit animal and human health. However, their physiological functions in bacterial and host physiologies are still controversial and not clear. In this review, we mainly discuss the current evidence related to the physiological roles that BSHs played in gut microbiota and human health, and the possible underlying mechanisms. Meanwhile, we also present the potential applications of BSHs and BSH-producing probiotics in various fields. Finally, we describe several important questions that need to be addressed by further investigations. A detailed exploration of the physiological significance of BSHs will contribute to their future diagnostic and therapeutic applications in improving animal and human health.